Wetland restoration suppresses microbial carbon metabolism by altering keystone species interactions - Zheng, Huijie; Liu, Deyan; Li, Ye; Chen, Zengming; Li, Junjie; Dong, Yanhong; Yang, Cong; Miao, Yuncai; Yuan, Junji; Ding, Weixin (Frontiers in Microbiology, 2025)
Soil bacteria play a pivotal role in regulating multifaceted functions of terrestrial ecosystems. Unraveling the succession of bacterial communities and the feedback mechanism on soil organic carbon (SOC) dynamics help embed the ecology of microbiome into C cycling model. However, how wetland restoration drives soil bacterial community assembly and species association to regulate microbial C metabolism remains unclear. Here, we investigated soil bacterial diversity, community structure and co-occurrence network, enzyme activities and SOC decomposition in restored wetlands for one, three, and four years from paddy fields in Northeast China. Wetland restoration for three and four years increased taxonomic (richness) and phylogenetic diversities by 2.39–3.96% and 2.13–3.02%, respectively, and increased the relative contribution of nestedness to community dissimilarity, indicating increased richness changed soil bacterial community structure. However, wetland restoration for three and four years decreased the richness index of aerobic Firmicutes by 5.04–5.74% due to stronger anaerobic condition characterized by increased soil Fe2+/Fe3+ from 0.20 to 0.64. Besides, wetland restoration for four years decreased network complexity (characterized by decreased node number by 2.51%, edge number by 9.62%, positive/negative edge number by 6.37%, average degree by 5.74% and degree centralization by 6.34%). Robustness index decreased with the increase of restoration duration, while vulnerability index increased with the increase of restoration duration, indicating that wetland restoration decreased network stability of soil bacterial communities. These results might be because stronger anaerobic condition induced the decrease of aerobic Bacilli richness index in keystone module, thereby reducing positive association within keystone module. Decreased positive species association within keystone module in turn weakened microbial C metabolism by decreasing hydrolase activities from 7.49 to 5.37 mmol kg SOC−1 h−1 and oxidase activities from 627 to 411 mmol kg SOC−1 h−1, leading to the decrease of SOC decomposition rate from 1.39 to 1.08 g C kg SOC−1 during wetland restoration. Overall, our results suggested that although wetland restoration after agricultural abandonment increased soil bacterial diversity, it decreased positive association within Bacilli-dominated keystone module under stronger anaerobic condition, which weakened microbial C metabolism and SOC decomposition.